2012
DOI: 10.1254/jphs.12008fp
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Blockade of <I>I</I><SUB>Ks</SUB> Destabilizes Spiral-Wave Reentry Under <I>&beta;</I>-Adrenergic Stimulation in Favor of Its Early Termination

Abstract: Abstract. We tested a hypothesis that an enhancement of I Ks may play a pivotal role in ventricular proarrhythmia under high sympathetic activity. A 2-dimensional ventricular muscle layer was prepared in rabbit hearts, and action potential signals were analyzed by optical mapping. During constant stimulation, isoproterenol (ISP, 0.1 μM) significantly shortened action potential duration (APD); chromanol 293B (30 μM), a selective I Ks -blocker, reversed the APD shortening. VTs induced in the presence of ISP last… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Studies show that high sympathetic nerve activity easily facilitates malignant ventricular tachyarrhythmias . Blocking I Ks can prevent proarrhythmic effects under the condition of high sympathetic tone, suggesting that enhancement of I Ks may play a pivotal role in ventricular proarrhythmia under high sympathetic activity …”
Section: Discussionmentioning
confidence: 99%
“…Studies show that high sympathetic nerve activity easily facilitates malignant ventricular tachyarrhythmias . Blocking I Ks can prevent proarrhythmic effects under the condition of high sympathetic tone, suggesting that enhancement of I Ks may play a pivotal role in ventricular proarrhythmia under high sympathetic activity …”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence showing that abnormal activity and modification of the sympathetic and parasympathetic functions are involved in the pathogenesis of AF (Khan et al, 2019 ). An interesting recent study reported by Kato (Kato et al, 2012 ) showed that, in rabbit ventricular myocardium, the spiral-wave reentry is maintained by β-adrenergic stimulation, likely through enhancement ofI Ks . Because this effect was reversed byI Ks inhibitor, the authors suggested that blockade of I Ks channels might be a promising therapeutic modality under conditions of high sympathetic activity.…”
Section: The Expression and Electrophysiological Properties Of I Ks I...mentioning
confidence: 95%